Pengaruh Inflasi, Nilai Tukar, dan BI Rate terhadap Volume Pertumbuhan Emisi Sukuk Korporasi di Indonesia - Almayda Rakhmadita; Destian Arshad Darulmalshah Tamara; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study is to analyze macroeconomic indicators that affect the growth volume of corporate sukuk emissions in Indonesia. Macroeconomic indicators used in this study are inflation, exchange rates and ithe BI rate. So the research object examined by the author is Inflation (X1), Kurs (X2), and BI Rate (X3) as independent variables and Corporate Sukuk Emissions in Indonesia (Y) as the dependent variable. The method used in this study is a quantitative research method with a descriptive approach. The author selects companies that issue corporate sukuk in Indonesia as a research sample. The data used in this study are secondary data on capital market statistics for the 2014-2018 period downloaded Otoritas Jasa Keuangan (OJK) website. The research model used is multiple linear regression analysis using windows-based data processing applications. The results of this study are that inflation has a negative and significant effect on the Growth Volume of Corporate Sukuk Emissions in Indonesia, Exchange Rate has a positive and significant effect on the Growth Volume of Corporate Sukuk Emissions in Indonesia, and the BI Rate does not significantly influence the Growth Volume of Corporate Sukuk Emissions in Indonesia.